2006
DOI: 10.1038/sj.onc.1209368
|View full text |Cite
|
Sign up to set email alerts
|

Using high-throughput SNP technologies to study cancer

Abstract: Identifying genes involved in the development of cancer is crucial to fully understanding cancer biology, for developing novel therapeutics for cancer treatment and for providing methods for cancer prevention and early diagnosis. The use of polymorphic markers, in particular single nucleotide polymorphisms (SNPs), promises to provide a comprehensive tool for analysing the human genome and identifying those genes and genomic regions contributing to the cancer phenotype. This review summarizes the various analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
80
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 89 publications
0
80
0
Order By: Relevance
“…In particular, a localized promoter of specific genes contributes to the cancer phenotype and regulates gene expression by disrupting or creating transcription factor sites or interfering with transcription factor binding (21). Our results demonstrate that LY6K expression is dependent not on the AP-1 transcription factor but on SNP242 by creating a de novo PAX-3 binding site that leads to a decrease in AP-1 binding affinity.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In particular, a localized promoter of specific genes contributes to the cancer phenotype and regulates gene expression by disrupting or creating transcription factor sites or interfering with transcription factor binding (21). Our results demonstrate that LY6K expression is dependent not on the AP-1 transcription factor but on SNP242 by creating a de novo PAX-3 binding site that leads to a decrease in AP-1 binding affinity.…”
Section: Discussionmentioning
confidence: 61%
“…SNPs are polymorphic markers that provide a comprehensive tool for analyzing the human genome and identifying specific genes and genomic regions linked to cancer phenotypes (21). Functional SNPs located on the promoter modulate gene expression leading to hormone or drug sensitivity and disease susceptibility (22,23).…”
mentioning
confidence: 99%
“…[25][26][27] Recently, the widespread presence of CNVs in the genomes of healthy individuals with no obvious genetic disorders has been described in a few populations, 1,2 but relatively few data has been reported regarding CNVs and disease resistance or susceptibility. 9,21 Regarding this point, the main aim of our work was to link the analysis of SNPs and CNVs within a worldwide framework to achieve a more powerful tool in the future determination of genetic basis of susceptibility or resistance to disease.…”
Section: Discussionmentioning
confidence: 99%
“…9 Electrochemical methods for detecting SNPs have received much attention. 8,9 Most of these approaches are based on the difference in thermal stability between mismatched and fully matched DNA duplexes.…”
Section: Introductionmentioning
confidence: 99%
“…9 Electrochemical methods for detecting SNPs have received much attention. 8,9 Most of these approaches are based on the difference in thermal stability between mismatched and fully matched DNA duplexes. 9 Barton and coworkers, [10][11][12][13] and Okamoto et al 14 reported a conceptually different electrochemical approach for detection of SNPs; the method relied on charge transport through the π-stack of duplexes on the surface of a gold electrode by combining redox-active intercalators with exogenous electrocatalytic species.…”
Section: Introductionmentioning
confidence: 99%